Faktor – Faktor Yang Mempengaruhi Kemiskinan Di Provinsi Kalimantan Tengah Tahun 2013-2022 - Alvin Alvin; Alexandra Hukom (Jurnal Ekonomi Manajemen Akuntansi, 2023)
Poverty is a serious problem for all countries, both developed and developing. The purpose of this study is to determine the impact of his GRDP, HDI and unemployment rate on poverty rate in Central Kalimantan from 2013 to 2022. The analytical tool used in this study is multiple regression analysis). The data used are time series and secondary data obtained from the Kalimantan Central Statistical Office (BPS) website Middle. The results of this study show that independent variables have a significant impact on poverty in Central Kalimantan. That is, the variables GRDP, Ipm, Unemployment, HDI and Unemployment variables have a negative impact on poverty in Central Kalimantan. The variables have a negative impact on poverty in Central Kalimantan.